An Analysis of Code-Switching in Ika Natassa’s Makna Talks Podcast Interview (Sastra Inggris UNPAM, 2025)
This study examined the phenomenon of code-switching in Ika Natassa’s speech on the Makna Talks podcast. Hoffman's (1991) theory was applied to identify the types of code-switching and the reasons for their use in Ika Natassa’s speech. A qualitative descriptive method was used to analyze utterances from the YouTube video transcript of the Makna Talks podcast. The study found 53 instances of code-switching. Intra-sentential switching was the most dominant type with 38 occurrences, followed by inter-sentential switching with 16 occurrences. Establishing continuity of the speaker appeared in 2 instances, while emblematic switching occurred only once. The most frequent reason identified in Ika Natassa’s speech was talking about particular topics, which occurred 34 times. Other reasons included quoting someone else, found in 5 instances, being emphatic about something, found in 3 instances, using interjections, found in 2 instances, and repetition for clarification, found in 3 instances. No instances of clarifying speech were identified, while expressing group identity appeared in 6 instances. Overall, the most dominant reason was talking about a particular topic. This study contributes to the sociolinguistic understanding of bilingual communication in digital media and highlights the influence of social and linguistic factors on language choice